Seed of Sarah: Memoirs of a Survivor - Isaacson, Judith Magyar
This gripping and highly acclaimed account of a young woman's experience in concentration camps now includes a final chapter, "A Time to Forgive?" detailing the author's trips back to her former forced labor camp in Germany.